ANALYSIS OF THE STRUCTURAL DEVELOPMENT AND PERFORMANCE OF THE FOOD, BEVERAGE, AND TOBACCO PROCESSING INDUSTRY IN KUPANG CITY (2021–2024) - Pereira, Lino; Yasri, Yasri; Rasyid, Rosyeni (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
The development of the food, beverage, and tobacco processing industry represents a key indicator of regional economic dynamics. This study examines changes in industrial structure and performance in Kupang City during the 2021–2024 period. The research population consists of all 1,913 processing industry business units operating in Kupang City, employing a total of 5,616 workers. A census approach was applied to analyze the entire population. Secondary data were obtained from official publications of Statistics Indonesia (BPS), the Ministry of Industry, and regional economic reports. Data analysis employed a quantitative descriptive method using trend analysis, tables, graphical illustrations, and annual growth rate calculations. The findings indicate a substantial increase in the number of enterprises from 1,107 units in 2021 to 1,913 units in 2024, with the most pronounced expansion occurring in 2023. Employment absorption rose from 3,260 to 5,616 workers over the same period. Investment value reached IDR 148.56 billion, while production value amounted to IDR 164.69 billion, reflecting strengthened production capacity and heightened investor confidence. Sectoral growth was driven by supportive government policies, MSME expansion, technological adoption, and rising market demand, although constraints related to raw material availability and infrastructure remain. These results provide empirical evidence to support local government strategies aimed at reinforcing the processing industry in the future. Keywords: processing industry; industrial structure; industrial performance; economic growth; Kupang City.